Problematika Orang Lansia tanpa Anak di dalam Masyarakat Minangkabau, Sumatera Barat - Edi Indrizal (Antropologi Indonesia, 2005)
The increasing of elderly proportion is now being a new challenge in Indonesian population. It needs further reinterpretation and comprehensive studies which uncover its interrelation with social organization system, tradition continuity and the dynamic of local community, so that the impact, of the growing number of the elderly can be explained. In this article the author explores the problems of elderly without children in Minangkabau society, well known as an ethnic matrilineal system and strong traditions of migration. The author identifies three categories of elderly without children in Minangkabau: childless elderly never got married, childless elderly due to reproductive failure, and the elderly not having children. The author also describes that elderly without children in Minangkabau face problems socially and psychologically, specifically relations between man and woman in matrilineal system, marriage relationship problems and migration. Key words: matrilineal society; children value; migration; social and economic impact.